(Re-)negotiating the process of staying in superdiverse places. Issue 3 (7th February 2023) - Pemberton, Simon
ABSTRACT: Little attention has been focused on how the differing features of 'superdiverse' neighbourhoods shape the demographic process of 'staying'. Through drawing on research conducted in two different superdiverse neighbourhoods in the city of Birmingham, UK, the paper highlights how 'staying' is an inherent feature of superdiverse neighbourhoods and which is actively practised by migrants and non-migrants alike. Empirically, the paper identifies how staying is informed by a number of features associated with superdiverse neighbourhoods, such as local infrastructure and visible population diversity, as well as relational proximity to other areas (of the city), including the significance of city centre spaces and their role as multicultural spaces of adaptation. Conceptually, the paper informs recent work on 'arrival infrastructures' and 'differentiated embedding' for migrant (and non-migrant) settlement and provides new insights into the territorial, relational and temporal aspects of staying. This includes the importance of neighbourhood histories in staying processes, and which hitherto have been relatively neglected.